The Relevance of Culture in Mandarin Reading Materials for Indonesian High School - Mirah Azizah; Ria Riski Marsuki (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2026)
Mandarin language learning is still largely dominated by the use of imported textbooks oriented toward Chinese culture. This condition often causes difficulties for students in understanding reading materials due to differences in cultural background from their daily lives. This article aims to analyze the importance of cultural relevance in Mandarin reading instruction for Indonesian high school students. Based on the results of a study involving 155 high school students, it was found that 64% of students found it easier to understand Mandarin reading texts that incorporated Indonesian culture compared to texts focused on Chinese culture. In addition, around 58% of students admitted that they were less interested in reading materials discussing foreign cultures that were far removed from their experiences, such as winter festivals and traditional Chinese family traditions. These findings indicate that cultural relevance in learning materials has a significant influence on students’ reading comprehension and learning motivation in Mandarin language learning. Therefore, the integration of Indonesian local culture into Mandarin learning materials is considered important in creating learning that is more contextual, meaningful, and aligned with the characteristics of Indonesian students.